Musculoskeletal pain among desk-based officials of Bangladesh: Association with mental health and individual factors. - Asif Iqbal Ahmed; Shahriar Hasan; Md Shahjalal; Rony Shaha; Mohammad Delwer Hossain Hawlader; Mohammad Morshad Alam (Public Library of Science (PLoS), 2023)
Musculoskeletal (MS) pain is widely prevalent and is an important health issue for desk-based employees which has a negative impact on both personal and work life. This study aimed to determine the MS pain status and its association with mental health and other individual factors among desk-based officials of Dhaka, Bangladesh. This cross-sectional study comprised a sample of 526 desk-based officials from Dhaka, Bangladesh. Data were collected between November 2020 to March 2021. MS pain was determined by the visual analog scale (VAS) and depression and anxiety were screened by Hospital Anxiety and Depression Scale (HADS). Logistic regression analyses were employed to estimate the adjusted effect of independent factors on MS pain. The overall prevalence of MS pain was 64% among desk-based officials. The corresponding prevalence were 19% severe, 21% moderate and 24% mild MS pain. In the adjusted model, gender (AOR: 0.19, 95% CI: 0.07-0.46), BMI (AOR: 0.28, 95% CI: 0.14-0.59), monthly income (AOR: 5.17, 95% CI: 2.18-12.25), organization type (AOR: 4.3, 95% CI:1.8-10.1), floor living (AOR: 4.7, 95% CI:2.1-10.8), physical activity (AOR: 0.16, 95% CI: 0.06-0.45), and lift facility in the house (AOR: 4.11, 95% CI: 2.06-8.23) were associated with MS pain. In addition, the prevalence of anxiety and depression was 17.7% and 16.4%, respectively. Depression was identified as a significant predictor for severe MS pain (AOR: 2.44, 95%CI:1.29-4.63). This study has revealed a relatively high prevalence of MS pain and mental health problems among Bangladeshi desk-based officials. Preventive measures need to be taken from both organizational and personal sides to delimitate MS pain and mental health problems.